Association Between Uric Acid and Worsening Peripheral Microangiopathy in Systemic Sclerosis - Pagkopoulou, Eleni; Soulaidopoulos, Stergios; Triantafyllidou, Eva; Malliari, Afrodite; Kitas, George D.; Garyfallos, Alexandros; Dimitroulas, Theodoros (Frontiers in Medicine, 2021)
Objective: The key element in the pathogenesis of systemic sclerosis (SSc) is microcirculatory changes in several vascular beds. Uric acid is associated with endothelial dysfunction and therefore microvascular damage. The aim of this study was to examine the association between uric acid (UA) and peripheral microvascular involvement in patients with SSc. Methods: We included consecutive, consenting patients with SSc. Serum UA, urea and creatinine were measured, and glomerular filtration rate (GFR) was calculated with CKD-EPI. All participants underwent nailfold video-capillaroscopy (NVC) to evaluate the microcirculation. Results: A total of 64 patients (95,3% women) were included in the study. UA levels were significantly associated with the number of avascular areas (r=0,290; p=0,020), whereas no correlation was shown for the GFR (r= -0,065; p=0,609). A significant trend of UA in the three capillaroscopic patterns was shown (3.90±1.52 vs 4.15±0.98 vs 5.38±2.26; for early, active and late patterns accordingly, p=0.028). Multivariate analysis showed that male gender (β=3.049; 95% CI= 0.997 - 5.101) and UA (β=0.352; 95% CI= 0.117 - 0.588) were independently associated with the number of avascular areas. Conclusions: These data suggest that UA levels are significantly associated with the capillaroscopic patterns, reflecting a progressive microvasculopathy.